RANCANGAN MEDIA HAIKU NO HAJIMARI SEBAGAI MEDIA ALTERNATIF PEMBELAJARAN NIHON BUNKASHAKAI NYUUMON - Eugenie Graceillia; Soni Mulyawan Setiana (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
This study aims to determine the design of the Haiku No Hajimari media application as an alternative media in learning Nihon Bunkashakai Nyuumon. This media was created using the Thunkable application. The method used in this research is the ADDIE model development method (Analysis, Design, Development, Implementation, and Evaluation). This media discusses the development of haikai starting from the Premodern era. In this discussion, there is an explanation of the Haiku No Hajimari media, starting from the design of the opening display to the credit menu. This media is designed to help students who are taking Nihon Bunkashakai Nyuumon courses in understanding Haiku material. The material in this media is taken from the book History of Japanese Literature written by Isoji Asoo, et al. The conclusion of this study is that the design of the Haiku No Hajimari media application has been successfully carried out and can run smoothly.